The hacker and the state cyber attacks and the new normal of geopolitics - Buchanan, Ben (Harvard University Press, 2020)
The threat of cyberwar can feel very Hollywood: nuclear codes hacked, power plants melting down, cities burning. In reality, state-sponsored hacking is covert, insidious, and constant. It is also much harder to prevent. Ben Buchanan reveals the cyberwar that’s already here, reshaping the global contest for geopolitical advantage